“SMART WASTE PROCESSOR” INOVASI PEMILAH DAN PENCACAH BAHAN MENTAH PUPUK DAN PLASTIK BERBASIS INTERNET OF THINGS - Yosita Lianawati; Christy Mahendra; Gerson Manuel Sugianto; Angelica Lulu Setiani; Altech Octaviaus; Brigita Maila Feriyani Wensen (LPPM Poltek ST Paul, 2023)
Waste management is one of the main challenges in protecting the environment and our health. Waste processing requires good and correct handling so as not to cause environmental pollution. This research aims to utilize the results of waste processing, especially organic and plastic waste, to reuse them. Waste processing in this research develops Internet of Things technology in monitoring the results of counting organic and plastic waste. The waste enumeration results are sent using the Callmebot API connected to the Whatsapp application. Testing of the Smart Waste system was carried out using the Proteus 8 simulation. From this test, the results showed that all components in the Smart Waste system ran well, and the simulation accuracy was 100%. Keywords: Smart Waste, Whatsapp, Internet of Things, Proteus 8